Odpowiedź:
a)
2 1/4 + x = 4
x = 4 - 2 1/4 = 1 3/4
b)
x - 3,6 = 8
x = 8 + 3,6 = 11,6
c)
-3 1/3 - x = 2
-x = 2 + 3 1/3 /*(-1)
x = -5 1/3
d)
2/5x = -4 /*5/2
x = -4 * 5/2 = -10
e)
x/4 = -2,8 /*4
x = -11,2
f)
-1,2x + x = 12,5
-0,2x = 12,5 /:(-0,2)
x = -62,5
g)
-6,5 - y = -3
-y = -3 + 6,5 /*(-1)
y = -3,5
h)
0,5y = -4,5 /:0,5
y = -9
i)
1/4y - 3 = 2
1/4y = 2 + 3 /*4
y = 5/4 = 1 1/4
j)
x/12 + 8 = -4
1/12x = -4 - 8 /*12
x = -12/12 = -1
k)
x + x - 1 = 3
2x = 3 + 1 /:2
x = 4/2 = 2
l)
2x - x + 4 1/2 = 8,5
x = 8,5 - 4,5 = 4
m)
4 = 2y - 5 - 3y
4 + 5 = -y
y = -9
n)
7y = 7 - 7y
7y + 7y = 7
14y = 7 /:14
y = 1/2
o)
6n = 0 /:6
n = 0
p)
3 2/3 = 1/2x - 1/3
1/2x = 3 2/3 + 1/3 /*2
x = 4 * 2 = 8
q)
69 - x = x + 96
x + x = 69 - 96
2x = -27 /:2
x = -27/2 = -13 1/2
r)
2 - x = 5 - 2x
-x + 2x = 5 - 2
x = 3
Szczegółowe wyjaśnienie: